Mapping Of Personalized Learning Environment (PLE) Among Malaysian‟S Secondary School - Che Pee @ Che Hanapi, Ahmad Naim; Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah (2014)
Integrating informal and formal learning by using social media in education context of the pedagogical approach is called as Personalized Learning Environment or PLE. This paper reports on the implementation of Personalized Learning Environment (PLE) among Malaysian’s secondary school. The purpose of this paper is to highlight (a) Personalized Learning Environment (PLE), (b) Why use PLE, (c) Elements in PLE, (d) Framework in PLE and (e) Issues with PLE. Several surveys were developed to explore the learning needs and goals as well as to construct the vision of PLE implementation. PLE is using a variety of social media in teaching students to become effective self-regulated learners. Besides that, it may help the students acquire basic and complex personal knowledge, management skills such as for creating, managing, and sustaining.